2015
DOI: 10.1186/s12900-015-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Binding of undamaged double stranded DNA to vaccinia virus uracil-DNA Glycosylase

Abstract: BackgroundUracil-DNA glycosylases are evolutionarily conserved DNA repair enzymes. However, vaccinia virus uracil-DNA glycosylase (known as D4), also serves as an intrinsic and essential component of the processive DNA polymerase complex during DNA replication. In this complex D4 binds to a unique poxvirus specific protein A20 which tethers it to the DNA polymerase. At the replication fork the DNA scanning and repair function of D4 is coupled with DNA replication. So far, DNA-binding to D4 has not been structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Specifically, the protein consists of a core β-sheet, made up of two anti-parallel β-strands, surrounded by two α-helices, one on the N′- and one on the C′-terminus of the central β-sheet (Schormann et al, 2007). Comparison of this crystal structure, as well as those of UDG in complex with uracil and dsDNA, to those available for human and E coli uracil DNA glycosylases, reveals that the catalytic pocket of UDG is nearly identical to other Family I members, including the conservation of two key catalytic residues, Asp68 and His181 (Schormann et al, 2013; Schormann et al, 2015; Schormann et al, 2007; Schormann et al, 2011; Schormann et al, 2016). In 2015, Schormann et al defined the D4 residues responsible for mediating protein-DNA interactions, with the interface being made up of Ile67, Pro71, Gly128, Glu129, Thr130, Lys131, Gly159, Lys160, Thr161, Asp162, Tyr180, His181, and Ala183.…”
Section: : Structural Analysis Of the D4 D4/dna D4/a20 D4/a20/dnamentioning
confidence: 88%
See 2 more Smart Citations
“…Specifically, the protein consists of a core β-sheet, made up of two anti-parallel β-strands, surrounded by two α-helices, one on the N′- and one on the C′-terminus of the central β-sheet (Schormann et al, 2007). Comparison of this crystal structure, as well as those of UDG in complex with uracil and dsDNA, to those available for human and E coli uracil DNA glycosylases, reveals that the catalytic pocket of UDG is nearly identical to other Family I members, including the conservation of two key catalytic residues, Asp68 and His181 (Schormann et al, 2013; Schormann et al, 2015; Schormann et al, 2007; Schormann et al, 2011; Schormann et al, 2016). In 2015, Schormann et al defined the D4 residues responsible for mediating protein-DNA interactions, with the interface being made up of Ile67, Pro71, Gly128, Glu129, Thr130, Lys131, Gly159, Lys160, Thr161, Asp162, Tyr180, His181, and Ala183.…”
Section: : Structural Analysis Of the D4 D4/dna D4/a20 D4/a20/dnamentioning
confidence: 88%
“…Several groups have undertaken a detailed investigation of the protein structure of D4 alone, in complex with the N′-terminus of A20 and/or in complex with DNA oligonucleotides (Burmeister et al, 2015; Contesto-Richefeu et al, 2014; Contesto-Richefeu et al, 2016; Sartmatova et al, 2013; Schormann et al, 2013; Schormann et al, 2015; Schormann et al, 2007). In 2007, the first crystal structure of the D4 uracil DNA glycosylase was published (Schormann et al, 2007).…”
Section: : Structural Analysis Of the D4 D4/dna D4/a20 D4/a20/dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Protein-protein interactions, in addition to protein-DNA interactions, may contribute to the association of these proteins with nascent DNA. For example, D4 can bind DNA (87,88) and, together with A20 (which has not been shown to bind DNA) and E9, forms a holoenzyme complex (23). H5 has affinity for DNA and interacts with both A20 (77) and the B1 protein kinase (77,89).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures have also been determined of UNG in complex with DNA from human [12][13][14], Vaccinia virus [15,16] and D. radiodurans [17]. These structures have revealed that the uracil is flipped out of the DNA and into the active site upon detection in a process where the enzyme binds the minor groove, compress the phosphate backbone and kink the DNA [13].…”
Section: Introductionmentioning
confidence: 99%